Investigation of Mechanical Properties of Graphene and Reduced Graphene Oxide Reinforced Epoxy Matrix Composites - Topal, E.; Parmak, E. Devrim Sam; Uzunsoy, D.; Cakir, O. Colak (AMER SOC TESTING MATERIALS, 2017)
Graphene has generated great excitement in the scientific community due its unique mechanical and electronic properties, and also the availability of bulk quantities of graphene as both colloidal dispersion and powder. With the development of relatively high yield and defect-free synthesis methods, this exciting material is ready for practical application in the preparation of polymer nanocomposites. Here, we reported on the mechanical performances of epoxy nanocomposites which have been reinforced with exfoliated graphene nano platelet (GNP) and reduced graphene oxide (RGO) at a loading of 0 to 0.5 wt. %. A soft molding method was used for the preparation of epoxy nanocomposites. The reinforcing effects of GNP and RGO on epoxy resin were examined by tensile testing and dynamic mechanical analysis (DMA). The morphology of the epoxy/GO and epoxy/RGO nanocomposites were investigated using a scanning electron microscope (SEM). A significant improvement on mechanical properties of epoxy/GO and epoxy/RGO nanocomposites was observed at low GNP and RGO loading. Contrary to the literature, the ultimate tensile strength values have mainly decreased, although the Young's modulus has improved. Dynamic mechanical analysis has shown that with the addition of both GNP and RGO, storage modulus was significantly enhanced at 40 degrees C. The loss factor was almost not affected by both RGO and GNP loading. SEM investigation of the fractured surface indicates that GNP and RGO fillers are dispersed uniformly in the epoxy matrix.
Keywords: Graphene nano platelets; reduced graphene oxide; dynamical mechanical analysis; tensile testing; CHEMICALLY-MODIFIED GRAPHENE; CARBON NANOTUBES; POLYMER; GRAPHITE; NANOCOMPOSITES; DISPERSION; EXFOLIATION; PLATELETS; Materials Science